Hubungan Self-Efficacy dengan Kemampuan Literasi Membaca Siswa dengan Menggunakan Model Problem Based Learning berbantuan Media Buku Saku - Indianasari Indianasari; Krisno Budi Prasetyo (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
This research was conducted to know the relationship between self-efficacy and students' reading literacy skills by using the Problem Based Learning model with the aid of pocketbook media. The type of research used is quasi-experimental or commonly called quasi-experimental. The type of research used is the quantitative method. The population of this study was all participants in class IV SDN Karangayau 02 the academic year 2018/2019 as many as 60 students were divided into 2 classes, namely class IV A and IV B. The sampling in this study used non-probability sampling with a saturated sampling technique. In collecting research data, students were given 2 research instruments, namely test instruments and non-test instruments. The test instrument is in the form of a description of reading literacy skills, while the non-test instrument is a self-efficacy questionnaire consisting of positive statements and negative statements. The data were tested for correlation. The data analysis technique used was correlation analysis with a significance level of 0.05. This research produces a correlation coefficient (r=0.850) with p=0.000 because it is smaller than the error rate (p<0.05), then the hypothesis is accepted. The results of data analysis show that there is a relationship between self-efficacy and reading literacy ability. Recommendations from this study, teachers should design a learning process that can increase students' self-efficacy so that students' reading literacy skills increase.